2023
DOI: 10.1093/jnci/djad008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically (un)healthy obesity and risk of obesity-related cancers: a pooled study

Abstract: Background Studies of obesity with or without metabolic aberrations, commonly termed metabolically unhealthy or healthy obesity, in relation to cancer risk are scarce. Methods We investigated body mass index (BMI, normal weight/overweight/obesity) jointly and in interaction with metabolic health status in relation to obesity-related cancer risk (n = 23,630) among 797,193 European individuals. A metabolic score comprising mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…). 35 This study concluded that metabolic dysfunction further increases ORC risk and may be a useful target for prevention in addition to obesity. Additionally, using UK Biobank data on 390,575 individuals, Cao et al 19 observed that MUO individuals had a higher risk of 10 ORCs, in contrast to MHO individuals that had a higher risk of only five ORCs.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…). 35 This study concluded that metabolic dysfunction further increases ORC risk and may be a useful target for prevention in addition to obesity. Additionally, using UK Biobank data on 390,575 individuals, Cao et al 19 observed that MUO individuals had a higher risk of 10 ORCs, in contrast to MHO individuals that had a higher risk of only five ORCs.…”
Section: Discussionmentioning
confidence: 79%
“…Other reports have observed associations of cancer with the metabolically unhealthy phenotypes, either with 11–13,34 or independent from obesity 14–21 . A recent pooled analysis of 797,193 participants in the Metabolic syndrome and Cancer (Me‐Can) project 2.0 observed statistically significant higher risks of ORC with all abnormal metabolic obesity phenotypes, with metabolically unhealthy obese individuals having the greatest risk ([OR (95% CI): 1.91 (1.74–2.09) and 1.43 (1.35–1.51), in men and women, respectively]) 35 . This study concluded that metabolic dysfunction further increases ORC risk and may be a useful target for prevention in addition to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10-30% of individuals with obesity maintain metabolic health characterised by an absence of conditions such as gallstones, diabetes, hyperinsulinemia, dyslipidaemia, or fatty liver 6 . These individuals may have lower cancer risks compared with their metabolically unhealthy counterparts, though risk remains higher than those who are metabolically healthy and lean 6,86 .…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…A large proportion of cancer cases in many regions and countries can be attributed to obesity and overweight 5 . Compared with metabolically healthy individuals with normal weight, metabolically healthy obese individuals have an approximately 30% increased risk of obesity‐associated cancers, while the risk is even more significant for metabolically unhealthy obese individuals 6 . In America, obesity has gradually surpassed tobacco as the leading preventable cancer cause 7 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Compared with metabolically healthy individuals with normal weight, metabolically healthy obese individuals have an approximately 30% increased risk of obesityassociated cancers, while the risk is even more significant for metabolically unhealthy obese individuals. 6 In America, obesity has gradually surpassed tobacco as the leading preventable cancer cause. 7 Prostate cancer (among males) and breast cancer (BC) (among females) have emerged as the leading types of cancer, surpassing lung cancer, as per the latest research data from the American Cancer Society.…”
Section: Introductionmentioning
confidence: 99%